ASSESSMENT OF SPECIFICITY OF FEATURES OF ACUTE APPENDICITIS IN CHILDREN UNDER 5 YEARS OF AGE - A.A. Akbaraliev; M. Ch. Abduvaliev; K. Z. Kadirov (Scholar Express Journals, 2022)
This article collects data on the occurrence of acute appendicitis in children under 5 years of age, which characterize the algorithm of physician's actions for diagnosis, treatment and prevention of this disease and help him quickly to make the right clinical decisions. They are intended to introduce the most effective and safe medical technologies into daily clinical practice, to prevent decisions on unwarranted interventions and thereby to improve the quality of medical care. These clinical guidelines are not aimed at the treatment of various forms of appendicitis.
Keywords: acute appendicitis; emergency surgery; clinical; children